The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.3917/ecop.187.0083
|View full text |Cite
|
Sign up to set email alerts
|

Le rôle des conditions de travail dans les absences pour maladie : le cas des horaires irréguliers

Abstract: Souvent négligées par la littérature économique, les conditions de travail sont susceptibles d’influencer les comportements d’activité. Cette étude s’intéresse en particulier à leur impact sur les absences pour maladie. Le modèle théorique développé dans une première partie suggère deux effets contradictoires : de mauvaises conditions de travail dégradent l’état de santé et accroissent les absences pour maladie, mais l’absentéisme peut être inversement freiné par un effet salaire, si les conditions de travail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These determinants include health status, gender, income level, working conditions, and sickness insurance. Economic research on absenteeism can be grouped into three categories (Afsa and Givord, ). The simplest of these models is the classic work‐leisure trade‐off model (Allen, ).…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These determinants include health status, gender, income level, working conditions, and sickness insurance. Economic research on absenteeism can be grouped into three categories (Afsa and Givord, ). The simplest of these models is the classic work‐leisure trade‐off model (Allen, ).…”
Section: Literaturementioning
confidence: 99%
“…Health‐related absenteeism is no longer an individual choice (work‐leisure trade‐off; effort function) but can be the result of deteriorating health status, either due to illness or difficult working conditions (Ose, ). Recent studies (Afsa and Givord, ) have effectively underlined the significant role of working conditions in employee absenteeism. Grignon and Renaud () dissociate sick leave, which is the result of employees’ choices ( ex post moral hazard), from absenteeism due to working conditions, which is the responsibility of the employer, by controlling for health status ( ex ante moral hazard).…”
Section: Literaturementioning
confidence: 99%
“…Using micro-data from the EU LFS 32 for 28 countries, Livanos and Zangelidis (2013) showed that a higher proportion of disabled persons (inactive and unemployed individuals) is associated to lower sickness absence, probably due to the pressure active people may experience. Afsa and Givord (2009), using French data, show that a high percentage of absenteeism among unskilled workers is, in fact, due to irregular working hours. Chaupain-Guillot and Guillot (op.…”
Section: Impact Of Health On Sick Leave 29mentioning
confidence: 99%
“…The determinants of sickness absence are potentially numerous and vary greatly over the publications: health status, gender, income level, working conditions and sickness insurance. Economic research on absenteeism can be grouped into three categories (Afsa and Givord, 2009).…”
Section: Determinants Of Sickness Absencementioning
confidence: 99%
“…Recent studies (Afsa and Givord, 2009) have effectively underlined the significant role played by working conditions in Employee absenteeism. Grignon and Renaud (2007) dissociated sick leave, the result of Employees' choices (ex post moral hazard), from absenteeism due to working conditions, which is the responsibility of the employer, by controlling for health status (ex-ante moral hazard).…”
Section: Determinants Of Sickness Absencementioning
confidence: 99%